SAT0352 Frequency of fractures and vitamin D serum levels in a cohort of HIV-1 infected patients. (23rd January 2014) - Ernst, D.; Stoll, M.; Schmidt, R.E.; Torsten, W.; Meyer-Olson, D.
Abstract : Background: An increased risk of hypovitaminosis D and/or fractures in HIV-infected patients has been discussed. We investigated the frequency of fractures and vitamin D serum levels in HIV-infected patients in a single university-based out-patient cohort in Germany. Methods: Charts of 1098 HIV-infected patients attending our out-patient clinic between 1/2004 and 06/2011 were screened for the presence of fracture at any location. Demographics and the presence of osteoporosis were then evaluated in these fracture patients. Measurement of the serum concentration of 25-OH- vitamin D3 was performed in 115 HIV-1 patients and 110 patients with Spondyloarthritis [SpA]. Results: In 71 out of 1098 HIV patients (6.4%) a fracture was diagnosed. Most experienced at least one fracture of the lower limb (29, 6%). The majority of these were located in the foot or ankle (66.7%). Other common fractures sites included the spine (16.9%) and the upper limb (15.5%). Average age at fracture was 51.84 years (±14.2 stdev). Recurrent fractures occurred in 11.3% of patients. Fractures after negligible or minor trauma occurred in 15 patients at a mean age of 56.9 years (±13.6 stdev). Diagnosis of osteoporosis occurred in 7 out of 71 patients (9.9%) with a mean age of 59.1 years (±6, 46 stdev). Four out of seven patients with osteoporosis were below 55 years and five out of seven were male. Decreased levels of 25-OH-vitamin D3 were detected in 81.2% of HIV-1 patients as compared to 61.8% of spondylarthritis patients (p=0.001). Conclusions: There is a high prevalence of fractures at different locations (most frequently the lower extremity) in HIV-1 infected patients. Fractures after a minor trauma and recurrent fractures were frequently observed in this cohort. HIV-1 seropositive patients osteoporosis was frequently diagnosed in males at a young age. In addition, we observed a higher prevalence of decreased 25-OH- vitamin D3 serum levels in this cohort of HIV-infected patients as compared to patients with spondyloarthritis. Disclosure of Interest: None Declared